Analisis Total Productive Maintenance dengan Menggunakan Metode Overall Equipment Efectiveness pada Mesin Injection Molding di PT. DEF - Nugroho, Pratama Syadi; Fasa, Nadia (Fakultas Teknik Universitas Tulang Bawang, 2026)
The application of Total Productive Maintenance (TPM) using the Overall Equipment Effectiveness (OEE) method at PT. DEF, The issue of maintenance has become crucial as it affects not only the reliability of the machines but also the speed and quality of production. This study will explore how the implementation of TPM using the OEE approach can improve machine effectiveness in a production environment, with a focus on timely and optimal maintenance strategies.The research aimed to assess the efficiency and effectiveness of machine operations, particularly injection molding machines, within the company's production line. Through the collection and processing of operational data, it was found that the OEE value for the machines in question ranged from 94% to 95%, surpassing the company's set standard of 93%. The high OEE score reflects effective machine utilization, availability, performance, and quality rates. The research highlights that while the current system meets international standards for machine maintenance, continuous improvements can further optimize machine productivity and reduce downtime. Keywords: Injection, Molding, OEE, TPM